Rhyzopertha dominica adult mortalities after exposure to indigenous Beauveria bassiana isolates from stored-grain pests: Effects of certain factors in sampling process. (June 2018) - Er, Mehmet Kubilay; Işikber, Ali A.; Aydin, Fadime; Ücük, Ceyda; Tunaz, Hasan
Abstract: In search for potential entomopathogenic fungi for microbial control of Rhyzopertha dominica, 75 Beauveria bassiana isolates previously recovered from stored-grain insects sampled in Adana and Mersin provinces of Turkey were tested and the mortality levels were used to evaluate possible effects of three sampling factors on encountering potential isolates. In the bioassays, twenty adults were exposed to 1000 ppm spores mixed into wheat kernels and adult mortalities after 14 days were used for statistical analysis. The relations between mortalities and 1) species of host insects from which isolates were obtained, 2) collection season –summer or autumn– of host insects from storage facilities, and 3) time of host insect's death –before or after collection– were evaluated. Considerable variations in mortalities were detected (13.67%–100%) depending on isolates. Amongst twelve Adana isolates, isolate 155657 caused the highest mortality. Eleven Mersin isolates were found to be effective against R. dominica . There was no correlation between R. dominica mortality and insect species from which isolates were obtained. Statistically, the frequency of potential isolates was higher in Adana samples collected in summer months compared to that in autumn months; however, sampling season did not have a significant effect in Mersin. The frequency of potential B. bassiana isolates was significantly higher when isolation was made from hosts that died in laboratory after sample collection compared to those isolated from hosts already dead at the time of collection. This study demonstrated that stored-grain insects are a good source of finding various B. bassiana isolates with different efficacy levels. At least for stored-grain insects, specifically sampling targeted species does not significantly increase the chance of finding highly potential isolates. However, retaining alive sampled insects can increase the likelihood of encountering isolates with high efficacy. Highlights: A wide range of efficacy was recorded amongst 75 indigenous isolates obtained from stored-product pests. Host insect species, from which fungi were isolated, did not affect the chance of finding potential isolates (efficacy ≥ 80%). More potential isolates were found from summer samples in Adana, but not in Mersin. Isolating fungi from hosts that died after collection resulted in higher numbers of potential isolates.